Conceptual model for assessing financial safety in the system of economic security of industrial enterprise - Metelenko, Natalia (Management and Entrepreneurship: Trends of Development, 2018)
The research is aimed at substantiating new approaches to the formation of the system of economic security and its components, in particular the financial component, in order to ensure the integrity of the system from the point of view of the possibility of effective functioning in new economic conditions, characterized by changes in the forms of interaction of industry with the banking system, the tax system; changes in the state policy, which complicate the mechanism of interaction with business structures. A set of scientific tasks aimed at achieving the goal of ensuring the economic security of an industrial enterprise is outlined. The scientists’ opinions on threats to the organization of economic security are generalized. It is proved that the financial security of an enterprise is central to the system of economic security, which is explained by the following: the level of financial security of any enterprise determines its ability to provide other components of its economic security, and changes in any field of the enterprise are ultimately reflected in its financial security. Internal threats to financial security by types of entrepreneurial activity are systematized and grouped. Based on the details of internal threats and risks of the economic activity of an industrial enterprise, an option is proposed for structuring objects and processes as components of the financial security system that are interconnected and interdependent. It is proved that the objects of financial security (constituents) are the functional activities of the enterprise, which are interconnected through the circulation of financial resources in the direction of achieving the goals of the enterprise. The advantages and disadvantages of methodical approaches to assessing the effectiveness of the financial security system of the industrial enterprise have been investigated, which made it possible to propose, as a methodological approach to the assessment of the effectiveness of the financial security system, the integrated use of such approaches: criterial, process - oriented and functional. The scientific significance of the work is that on the basis of the integrated methodical approach a conceptual model of analytical estimation of the level of financial security in the system of economic security of the industrial enterprise is developed.